2013
DOI: 10.1007/978-3-642-41184-7_72
|View full text |Cite
|
Sign up to set email alerts
|

A Graph-Based Method for PET Image Segmentation in Radiotherapy Planning: A Pilot Study

Abstract: Abstract. Target volume delineation of Positron Emission Tomography (PET) images in radiation treatment planning is challenging because of the low spatial resolution and high noise level in PET data. The aim of this work is the development of an accurate and fast method for semi-automatic segmentation of metabolic regions on PET images. For this purpose, an algorithm for the biological tumor volume delineation based on random walks on graphs has been used. Validation was first performed on phantoms containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Therefore, further studies are planned to use a multimodal approach to the target volume contouring, which integrates MRI with MET‐PET ([ 11 C]‐labeled Methionine ‐ Positron Emission Tomography) imaging (Levivier et al, ). In this way, MR images will highlight the morphology of the lesion volume (GTV), while PET images will provide information on metabolically active areas (Biological Target Volume, BTV; Stefano et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further studies are planned to use a multimodal approach to the target volume contouring, which integrates MRI with MET‐PET ([ 11 C]‐labeled Methionine ‐ Positron Emission Tomography) imaging (Levivier et al, ). In this way, MR images will highlight the morphology of the lesion volume (GTV), while PET images will provide information on metabolically active areas (Biological Target Volume, BTV; Stefano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are planned to use a multimodal approach to the target volume contouring, which integrates MRI with MET-PET ([ 11 C]-labeled Methionine -Positron Emission Tomography) imaging (Levivier et al, 2002). In this way, MR images will highlight the morphology of the lesion volume (GTV), while PET images will provide information on metabolically active areas (Biological Target Volume, BTV; Stefano et al, 2013). The proposed approach for lesion segmentation from brain MRI, properly integrated with PET segmentation, would provide a comprehensive support for the accurate identification of the region to be treated with the high precision radiation therapy approach.…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric and semi-quantitative parameters were extracted using a software package that has been developed and implemented ‘ ad hoc ’ by our group to assess treatment response in oncological patients: PET parameters were measured on the lesions that had previously been identified as suspicious by visual analysis using our automatic segmentation algorithm based on random walks on graphs ( 37 ). The nuclear medicine physician interactively selected the PET region with uptake higher than the background, excluding any physiological uptake findings, by clicking on the image.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this issue, the RW algorithm is capable of performing the segmentation. For this reason, starting from our previous study (Stefano et al, ), parameters in (1) have been modulated to incorporate metabolic information in the original RW algorithm: g i and g j have been replaced with the standardized uptake value (SUV) in the voxels i and j , wij = exp(β(SUViSUVj)2) where SUV = M/(I/W) …”
Section: Methodsmentioning
confidence: 99%
“…So, RW is an efficient and accurate method in low contrast images characterized by noise and weak edges such as PET images (Boellaard et al, 2004;Zaidi and El Naqa, 2010): the behavior of the RW algorithm in the presence of these issues distinguishes it from other approaches (Grady, 2006). Even if the study proposed by Rzeszutek et al (2009) affirms that a drawback to RW algorithm is that it has difficulty producing clean segmentations in the presence of noise, in previous PET studies (Bagci et al, 2011;Stefano et al, 2013;Onoma et al, 2014) the RW method showed accurate results in the delineation of metabolic targets. For these reasons, we propose a fully automatic and operator independent method for the BTV delineation of brain metastases for Gamma Knife treatments based on an extension of the RW algorithm.…”
Section: Introductionmentioning
confidence: 99%